2018
DOI: 10.3390/ijerph15122711
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Impact of Cognitive Function on Health Literacy among Older Adults with Heart Failure

Abstract: Heart failure (HF)-related cognitive decline is a common condition and may be associated with health literacy. However, gender differences in this context have not been explored fully. This secondary data analysis aimed to identify gender differences in the impact of cognitive function on health literacy among older patients with HF. A total of 135 patients (75 men and 60 women) with a mean age of 73.01 ± 6.45 years were recruited. Older women with HF had higher cognitive impairment (15%) and inadequate health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 37 publications
2
22
1
Order By: Relevance
“…This result was associated with a previous study that found that women with mild cognitive impairment have greater longitudinal rates of cognitive and functional progression than men [42]. In one study concerning patients with heart failure [43], cognitive impairment was more prevalent among older women than men. Likewise, there have been reports that women have a higher prevalence of multimorbidity than men despite their longer life spans [44,45].…”
Section: Discussionsupporting
confidence: 63%
“…This result was associated with a previous study that found that women with mild cognitive impairment have greater longitudinal rates of cognitive and functional progression than men [42]. In one study concerning patients with heart failure [43], cognitive impairment was more prevalent among older women than men. Likewise, there have been reports that women have a higher prevalence of multimorbidity than men despite their longer life spans [44,45].…”
Section: Discussionsupporting
confidence: 63%
“…Moreover, because of the very low proportion of women in our sample, we were unable to discuss sex-related differences. Yet according to Lee et al [ 62 ], older women with HF had higher CI (15%) and more inadequate health literacy (56.7%) compared to men. In their study, cognitive function was the strongest predictor of health literacy in men (β = 3.668, p < 0.001) and women (β = 2.926, p = 0.004).…”
Section: Discussionmentioning
confidence: 99%
“…According to their findings, males and older individuals tend to have slightly lower health literacy, while a higher level of education is a strong positive predictor of health literacy 20 . Besides, regarding health literacy, several other studies state these gender, age and education significant differences, reporting that an increase in age, being male and lower levels of education usually implies a decrease in health literacy , [21][22][23][24][25][26][27] .…”
Section: Discussionmentioning
confidence: 99%